The Role of Teachers in Improving Early Childhood's Religious Values - Astria Liani, Tika; Khotimah, Husnul; Arifin, Zaenal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the role of teachers in fostering religious values in early childhood within a formal educational setting. This study employed a qualitative approach with descriptive methods to gain a deep understanding of religious learning practices implemented by teachers. Data collection techniques included observation of learning activities, in-depth interviews with teachers, and documentation studies relevant to the early childhood religious education process. The data obtained were analyzed using qualitative analysis techniques, including data reduction, data presentation, and systematic conclusion drawing. Data validity was ensured through diligent observation and triangulation of data collection techniques. The results indicate that teachers play a strategic role in strengthening religious values in early childhood, manifested through their understanding of basic religious concepts, the implementation of habitual worship practices, the use of varied and contextual learning strategies, and modeling religious attitudes and behaviors in daily life within the school environment. These findings confirm that optimizing the role of teachers significantly contributes to the internalization of religious values in early childhood and is a crucial factor in the formation of religious character from an early age.